The effects of ulimorelin, a ghrelin agonist, on liquid gastric emptying and colonic transit in humans. Issue 3 (3rd February 2020) - James, Joyce; Mair, Stuart; Doll, Walter; Sandefer, Erik; Wurtman, David; Maurer, Alan; Deane, Adam M; Harris, M. Scott
Abstract: Background: Ulimorelin, a small molecule ghrelin agonist and prokinetic agent, was effective in animal models of gastroparesis and delayed transit. However, employing once daily administration, it failed in clinical trials of postoperative ileus (POI), a condition in which colonic motility recovers last. The aim of this study was to evaluate drug dosing and regional differences in drug activity between stomach and colon. Methods: Gastric emptying was assessed by scintigraphy in healthy adults at single doses of 600‐1200 µg kg −1 and multiple doses of 80‐600 µg kg −1 Q8H for 7 days. Colonic motility was assessed by 7‐region scintigraphic analysis at a dose of 600 µg kg −1 for 2 days. The primary endpoints were percent change in time to 50% (∆ t 50 ) liquid gastric emptying on Days 1, 4, and 6 and the geometric mean center of colonic transit at 24 hours (GC24 ). Plasma concentrations of free and total ulimorelin were measured for pharmacokinetic and exposure‐response modeling. Key Results: Ulimorelin 150‐600 µg kg −1 every 8 hours resulted in statistically significant improvements (∆ t 50  = 23% to 46% ( P  < .05)) in gastric emptying from baseline that were sustained through Day 6. However, no effects on GC24 were observed. Pharmacokinetic analyses suggested that the free concentrations of ulimorelin achieved in POI trials and dosing frequency may have been inadequate. Conclusions and Inferences: Ulimorelin is a potent gastric prokinetic but lacks evidence of activity in the human colon, pointing to the stomach as the predominant site of action of ghrelin in humans; ClinicalTrials.gov NCT02993055. Abstract : Exposure response for ulimorelin on Day 1 and Day 4 of drug administration in healthy volunteers, demonstrating similar effects on gastric emptying (changes (Δ) in 50% emptying times).